Становлення і розвиток муніципальної влади у Волинській області (1990–2010 рр.) - Малиновський, Валентин Ярославович; Malynovskyi, Valentyn YA. (Рівненський державний гуманітарний університет, 2013)
У статті здійснено періодизацію процесу становлення і розвитку муніципальної влади у Волинській області за двадцятилітній період, з 1990 р. – перших демократичних виборів і початку роботи рад першого демократичного скликання до 2010 р. – діяльності органів місцевого самоврядування п’ятого скликання. На основі політико-правового аналізу автором виокремлено сім етапів еволюції муніципальної влади в регіоні та охарактеризовано кожен з них.

Article include stheperiodization the formation and development of municipal authoritiesin the Volyn region for the period of twenty years, from 1990 - the first democratic elections and beginning the activities of the first democratic councils before 2010 – the activities of local government of the fifth convocation. Authordivided the evolution ofmunicipal authoritiesin the region based on the political and legal analysis of the historical period into seven stages: the first - 1990-1992; second - 1992-1994, the third 1994-1995, fourth 1995-1996; five 1996-2004, sixth 2004-2006, seventh 2006-2010. The article includes each of these stages, particularly in the context of the existing electoral system, the results of the local elections, the model of territorial organization of public authority, competence of the public authorities, the relationship of local governments and authorities and issues between them, processes democratization in Ukraine. Author made a focuson the shortcomingsof the nationalmodelofmunicipal authorities,including theabsence ofa regionalgovernment taking thelocalgovernmentsin the Volyn region for the example. On this basis authormade a conclusion that local government in the Volyn region for the set time has passed a difficult way from the Soviet system of government to form an independent public authority. However, it did not become effectivemunicipal authoritiesinstitution, which carries out public order on the effective management of local affairs.
The formation and development of municipal authoritiesin the Volyn region(1990–2010 years)
Keywords: муніципальна влада; місцеві вибори; виборча система; орган місцевого самоврядування; депутат місцевої ради; municipal authorities; local elections; electoral system; local government; member of the local council